A Ring‐Distortion Strategy from Marine Natural Product Ilimaquinone Leads to Quorum Sensing Modulators. Issue 20 (14th April 2018) - Evanno, Laurent; Lachkar, David; Lamali, Assia; Boufridi, Asmaa; Séon‐Méniel, Blandine; Tintillier, Florent; Saulnier, Denis; Denis, Stéphanie; Genta‐Jouve, Grégory; Jullian, Jean‐Christophe; Leblanc, Karine; Beniddir, Mehdi A.; et al.
Abstract : We report herein a ring‐distortion strategy applied to marine natural substances ilimaquinone and 5‐ epi ‐ilimaquinone. A chemically diverse library of molecules was synthesised that included rearrangements of the sesquiterpene moiety and original reorganisations of the quinone ring. Chemoinformatic analyses evaluated the rise of structural diversity and the exploration of chemical space. Some focussed biological activities of this library were also investigated; quorum sensing activity of Vibrio harveyi was envisaged and some of the new compounds were shown to be good quorum sensing inhibitor candidates, whereas others were activators. Toxicities were also evaluated and some products showed micromolar activities against human umbilical vein endothelium, human hepatocellular carcinoma and human lung carcinoma (A549) cells. Abstract : A ring‐distortion strategy is applied to ilimaquinone and 5‐ epi ‐ilimaquinone. A diverse compound library was synthesised that included rearrangements of the sesquiterpene moiety and the quinone ring. Quorum sensing activity of Vibrio harveyi was evaluated and some of the new compounds were shown to be good quorum sensing inhibitor candidates.